Identify the Causes of Absenteeism in Nurses Mayo Hospital Lahore Pakistan - Kanwal, Nabila; Riaz, Ghazala; Riaz, Muhammad Shahid; Safdar, Shoumaila (International Journal of Social Sciences and Management, 2017)
Absenteeism is a usual pattern of absence from a duty or responsibility. Usually, absenteeism is considered as an indication of person poor performance. In this study a descriptive cross sectional study design was used. A close ended questionnaire was used as a research tool. Convenient sampling technique was used. Data was analyzed on SPSS 20 version. Nurses are absent from their duties because they suffer from minor ailments e.g. headache and backache? In response of this question, 42.5% responded said that they are strongly agreed, 17.5% were agreed, 8.8% were neutral, 21.3% were disagreed, and 10% were strongly agreed. Nurses do absent from their work because workload is too heavy, 42.5% were agreed, 30% were strongly agreed, 12.5% were neutral,7.5% were disagreed and 7.5% were also strongly disagreed. The lack of appropriate recognition and reward could lead to dissatisfaction and absenteeism among nurses, in response of this question nurses asked that they do absent 31.3% agreed, 41.3% strongly agreed, 15.0% are neutral, 12.5%are disagreed and 0% are strongly disagreed. Staff absenteeism is a growing management concern. It can contribute to sickness absence, staffing instability, work overload and job dissatisfaction that could have a negative impact on patient care. The rate of absenteeism can be reduced by productive management, and loyal leadership. It will not only reduce absenteeism rate but also improve quality of care toward the patients. In return of good performance nurses need appraisal. Int. J. Soc. Sc. Manage. Vol. 4, Issue-2: 110-114